Gene editing technology to improve antitumor T-cell functions in adoptive immunotherapy - Yusuke Ito; Satoshi Inoue; Yuki Kagoya (Inflammation and Regeneration, 2024)
Abstract Adoptive immunotherapy, in which tumor-reactive T cells are prepared in vitro for adoptive transfer to the patient, can induce an objective clinical response in specific types of cancer. In particular, chimeric antigen receptor (CAR)-redirected T-cell therapy has shown robust responses in hematologic malignancies. However, its efficacy against most of the other tumors is still insufficient, which remains an unmet medical need. Accumulating evidence suggests that modifying specific genes can enhance antitumor T-cell properties. Epigenetic factors have been particularly implicated in the remodeling of T-cell functions, including changes to dysfunctional states such as terminal differentiation and exhaustion. Genetic ablation of key epigenetic molecules prevents the dysfunctional reprogramming of T cells and preserves their functional properties. Clustered, regularly interspaced, short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas)-based gene editing is a valuable tool to enable efficient and specific gene editing in cultured T cells. A number of studies have already identified promising targets to improve the therapeutic efficacy of CAR-T cells using genome-wide or focused CRISPR screening. In this review, we will present recent representative findings on molecular insights into T-cell dysfunction and how genetic modification contributes to overcoming it. We will also discuss several technical advances to achieve efficient gene modification using the CRISPR and other novel platforms.